Femoral fixation methods for hamstring graft in anterior cruciate ligament reconstruction: A network meta-analysis of controlled clinical trials. - Shixin Nie; Shuqing Zhou; Wei Huang (PLoS ONE)
Objective To compare the clinical effectiveness of cortical button (CB), cross-pin (CP) and compression with interference screws (IS) fixation techniques in anterior cruciate ligament (ACL) reconstruction using hamstring graft. Methods Studies were systematically retrieved from PubMed, Embase, Cochrane Library and Web of Science up to May 20, 2021. Primary outcomes were KT-1000 assessment, International Knee Documentation Committee (IKDC) score A or B, Lachman's test, pivot-shift test, visual analogue scale (VAS) score, Lysholm score, Tegner score, and Cincinnati Knee Score. Secondary outcomes included reconstruction failures and synovitis. League tables, rank probabilities and forest plots were drawn for efficacy comparison. Results Twenty-six controlled clinical trials (CCTs) with 1,824 patients undergoing ACL reconstruction with hamstring graft were included. No significant differences were found among CB, CP and IS fixation methods regarding the 10 outcomes. For KT-1000 assessment, IKDC score A or B, Lachman's test, VAS score and pivot-shift test, CP had the greatest probability of becoming the best method, and IS may be the suboptimal method in 4 out of these 5 outcomes except pivot-shift test. Conclusions CP, CB and IS fixations have comparable clinical performance, while CP fixation is most likely to be the optimum fixation technique for hamstring graft in ACL reconstruction. Future larger-sample studies of high quality comparing these techniques in more clinical outcomes are required.